Phytochemical and Bioactive Profile of Medicinal Plants Used Traditionally in Bosnia and Herzegovina - Ibragic, Saida; Mesinovic, Aisa; Arnaut, Selma; Delic, Emina; Besta-Gajevic, Renata; Dahija, Sabina; Dizdar, Muamer; Karalija, Erna (Natural Products Journal, The, 2024)
Introduction: This paper aimed to characterize the phytochemical profile and bioactivities of 22 plant species used in the traditional medicine of Bosnia and Herzegovina. The utilization of plants in traditional medicine in Bosnia and Herzegovina holds significant importance, not only as a reflection of cultural heritage but also as a sustainable and time-tested approach to healthcare, fostering a harmonious connection between nature and well-being. Method: The comprehensive analyses encompassed the determination of total phenolic and flavonoid content, alongside assessing antioxidant activity using DPPH and FRAP assays. Additionally, antimicrobial activity was tested against S. aureus. ssp. aureus, MRSA, P. aeruginosa, S. abony and C. albicans. Many of the analyzed plant extracts showed a high phenolic content (C. avellana, V. myrtillus) and antioxidant activity (C. avellana, V. myrtillus, B. pendula, S. officinale, E. angustifolium, J. globifera ssp. hirta). Result: The majority of extracts showed good antimicrobial activity against S. aureus ssp. aureus and MRSA. The E. angustifolium extract was effective against all tested bacterial strains, with MIC values ranging from 1.25-10 mg/mL. The research identified significant levels of secondary metabolites and plant species with potent antioxidant and antimicrobial activity. Conclusion: The study also revealed significant correlations among various phytochemical parameters and bioactivities.
Keywords: medicinal plants